The Cold War: an ideological conflict (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The Cold War was a conflict of competing ideologies, which consumed global politic throughout the 20th century. While it was ostensibly fought between the Soviet Union and the United States of America, The rest of the world was also forced to pick sides in this clash of superpowers. While weapons of mass destruction were stockpiled on both sides, many small wars were fought worldwide. This international conflict brought mankind to the brink and its impact is still being felt today.